Agro-pastoral production system of Egypt. Climate change, vulnerability and opportunities for poverty alleviation - Metawi H.R.M. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Agro-pastoral production system in the northwestern coastal zone of Egypt is characterized by varied agricultural activities including raising small ruminant's flocks, beside cultivation of barley and some fruits as Olives and Figs. This system has been fragilized by drought that has become more frequent and worsened by human activities. A survey study was conducted to identify and analyze the causes, impacts and management mechanisms of drought crisis in this area. The sample of the study encompassed 162 agropastoralists. Major findings were extracted for the causes of drought vulnerability included socio- economic, livelihood and agriculture. The annual income of the household reduced by 58.3% in the drought years. The various Bedouins coping mechanisms were inadequate to reduce the negative impact of drought. Results highlight small ruminant role on alleviating poverty and helping household to deal with climate variability. The share of small ruminant in the households economy in the dry year ranged from 60%-67%.The perception of small ruminant to escape poverty is completely linked to the flock size. Based on the findings and conclusions of this study, specific recommendations were made to reduce effects of drought crisis.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)